RATING ANALYSIS OF THE LEVEL OF DIGITAL TRANSFORMATION OF THE ECONOMIES OF EAEU AND EU THE COUNTRIES - G. G. Goloventchik (Цифровая трансформация, 2018)
The article considers the problem of assessing the level of development in the country of the digital economy with the help of international ICT ratings, their shortcomings are analyzed. Based on the methods studied, the original rating system for evaluating the development of the digital economy has been formed, including 22 indicators, combined into five subindexes. The developed method for assessing the effectiveness of ICT use in various fields of activity has been tested in some countries of the EAEC and the EU. Based on the results of the analysis, the main problem areas were identified, which should be addressed to ensure the growth of Belarus indicators in the world ICT ratings.